2018
DOI: 10.1186/s12881-018-0672-z
|View full text |Cite
|
Sign up to set email alerts
|

Upper limb muscle overgrowth with hypoplasia of the index finger: a new over-growth syndrome caused by the somatic PIK3CA mutation c.3140A>G

Abstract: BackgroundScientists have previously described an overgrowth syndrome in Saudi patients and named it ‘Upper limb muscle overgrowth with hypoplasia of the index finger’ syndrome.Case presentationWe describe a new case and document that the syndrome is caused by the somatic PIK3CA mutation c.3140A>G, p.His1047Arg. We also recruited one of the previously reported cases and found the same somatic mutation in the affected muscles. A wider classification of ‘PIK3CA-related pathology spectrum’ is presented which incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Aberrant accessory muscles have also been reported in other surgically treated patients with upper limb muscle hypertrophy and in some cases of carpal tunnel syndrome, but no genetic analysis of aberrant muscles have been performed to rule out somatic mosaic PIK3CA mutations. To the best of our knowledge, there are three patients previously described with isolated upper limb muscle overgrowth and with a confirmed PIK3CA mutation . In 2014, Castiglioni et al reported the first mosaic PIK3CA mutation in a patient with unilateral isolated muscular hypertrophy of the left hand and arm and aberrant muscles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Aberrant accessory muscles have also been reported in other surgically treated patients with upper limb muscle hypertrophy and in some cases of carpal tunnel syndrome, but no genetic analysis of aberrant muscles have been performed to rule out somatic mosaic PIK3CA mutations. To the best of our knowledge, there are three patients previously described with isolated upper limb muscle overgrowth and with a confirmed PIK3CA mutation . In 2014, Castiglioni et al reported the first mosaic PIK3CA mutation in a patient with unilateral isolated muscular hypertrophy of the left hand and arm and aberrant muscles.…”
Section: Discussionmentioning
confidence: 99%
“…3 The variable expression of symptoms within PROS is mainly explained by the timing and location of the initiating PIK3CA mutation, but the reason behind the high degree of interindividual phenotypic heterogeneity is unknown. 7,8 Somatic activating PIK3CA mutations are common in at least 12 different cancer types. 5 It has been proposed that an increased number of neuromuscular junctions and a change in the muscle-tendon ratio is involved in muscle hypertrophy development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another interesting feature of the phenotype in our series is the presence of the malformations in the upper limbs only. An isolated muscle overgrowth syndrome (without any vascular malformations) confined to the upper limbs and linked to somatic P1K3CA mutations has been described (Al-Qattan et al., 2018). The reason for the confinement of these lesions to the upper limb remains a mystery.…”
Section: Discussionmentioning
confidence: 99%